Association of perceived environmental characteristics and participation in organized and non-organized physical activities of adolescents - Mota, J. (2009)
Specific behavior context Such as type of PA (organized vs. nonorganized) might be associated with different environmental correlates. The main goal of this cross-sectional survey was to examine perceived environmental associations with type of adolescents' physical activity (PA) choices (organized and nonorganized). A sample of this study comprised 425 girls with mean age of 14.5 years-old. Environmental variables and PA were assessed by questionnaire, which allowed to define the type (organized or nonorganized) of PA. No associations were found between environmental perceptions and the participation in organized activities. However, different dimensions of environmental variables such as accessibilities to facilities (p <= .05) aesthetics (p <= .05) and social environment (p <= 05) were associated to girls' PA participation in nonorganized activities (NOPA). Our findings suggested that some environmental characteristics might play an important role in girls' NOPA participation.